2001
DOI: 10.1590/s0100-06832001000300001
|View full text |Cite
|
Sign up to set email alerts
|

Resistência mecânica à penetração de um Planossolo submetido a diferentes sistemas de cultivo

Abstract: RESUMOO conhecimento das características e propriedades dos solos de várzea do RS, utilizados atualmente com a cultura do arroz irrigado, torna-se essencial para a adoção de práticas que envolvam irrigação, drenagem, correção da acidez e da fertilidade, principalmente quando se deseja obter altos níveis de produtividade, com menor custo e com menores possibilidades de degradação destes solos e do ambiente onde estão situados. Dentro deste panorama, avaliouse a compactação de um Planossolo cultivado sob diferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
1
9
0
17
Order By: Relevance
“…Thus, a denser soil layer in the areas of Experiment 1 may also be associated with the systematization process of the area. In addition, the study carried out by Pedrotti et al (2001), evaluating the compaction of an Albaqualf soil under different management systems, found that all of the tillage systems evaluated had soil mechanical resistance to penetration values higher than 2.0 MPa, especially in the 0.1-0.2 m layer, and maximum resistance values were observed in the management system with continuous irrigated rice crops. According to the same author, conventional tillage contributes to physical degradation of the soil due to increased soil mechanical resistance to penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a denser soil layer in the areas of Experiment 1 may also be associated with the systematization process of the area. In addition, the study carried out by Pedrotti et al (2001), evaluating the compaction of an Albaqualf soil under different management systems, found that all of the tillage systems evaluated had soil mechanical resistance to penetration values higher than 2.0 MPa, especially in the 0.1-0.2 m layer, and maximum resistance values were observed in the management system with continuous irrigated rice crops. According to the same author, conventional tillage contributes to physical degradation of the soil due to increased soil mechanical resistance to penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Pedrotti et al (2001), a resistência à penetração serve para descrever a resistência física que o solo oferece a algo que tenta se mover através dele. Ela está diretamente correlacionada com vários atributos e condição do solo, como textura, densidade, matéria orgânica e, principalmente, a umidade (θ) no momento da determinação (Stolf et al, 1983;Busscher et al, 1997).…”
Section: Introductionunclassified
“…A qualidade física do solo para o desenvolvimento das plantas é determinada, dentre outros fatores, pela resistên-cia do solo à penetração das raízes, sendo um atributo que merece destaque, já que atinge diretamente o desenvolvimento das plantas (Pedrotti et al, 2001). De acordo com Genro Junior et al (2004) e Silva et al (2004 a resistência do solo à penetração geralmente é influenciada pelas condições do manejo e a intensidade de tráfego de máquinas agrícolas.…”
Section: Introductionunclassified